Parasitisme Sosial dan Budaya: Studi Kasus tentang Dinamika Hubungan Etnis Batak dan Melayu di Deli Serdang - Nuriza Dora; Yemmi Sofia Ginting; Wafiq Nurhalizah; Khairunnisa Sitompul (Badan Penerbit STIEPARI Press, 2025)
This study examines the phenomenon of social and cultural parasitism in the context of ethnic relations between the Batak and Malay communities in Deli Serdang Regency, North Sumatra, Indonesia. Social and cultural parasitism is reflected in patterns of dominance, wherein one ethnic group gains disproportionate access to economic, social, and symbolic resources, often at the expense of the other. The objective of this research is to analyze how such forms of dominance emerge, persist, and contribute to structural inequality and potential interethnic tensions.Adopting a qualitative approach and employing a case study method, the research investigates various dimensions of dependency within everyday social interactions. The analysis is grounded in Social Conflict Theory and Social Capital Theory to uncover underlying mechanisms that perpetuate inequality and group stratification.Findings reveal that the Batak community’s economic and symbolic dominance reinforces the marginalization of the Malay community, a condition further intensified by historical legacies and local policy dynamics. The study proposes strategic recommendations for inclusive policy-making, interethnic social capital development, and culturally sensitive adaptation efforts aimed at fostering social harmony and equitable integration within a multicultural society.